2021
DOI: 10.3390/met11081306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of V Addition on Microstructure and Mechanical Properties in C–Mn–Si Steels after Quenching and Partitioning Processes

Abstract: Three C-Si-Mn Q&P steels with different V addition after one-step and two-step quenching and partitioning (Q&P) processes were investigated by means of optical microstructure observation, X-ray diffraction (XRD) measurement, transmission electron microscopy (TEM) characterization and particle size distribution (PSD) analysis. The effect of V addition on strength and ductility of the steels was elucidated by comparative analysis on the microstructure and mechanical properties as functions of partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…These elements are known to form carbides that may refine the PAGS on the event the precipitate dissolution temperature is not reached [110] and therefore both the martensite and bainite structure will be refined. In addition, austenite could be strengthened through grain boundary strengthening and precipitation hardening leading to increased volume fraction of retained austenite [111,112]. However, the carbon content of the retained austenite may decrease because of the carbide precipitates [111,112], in turn increasing the driving force for bainite formation.…”
Section: Influence Of Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…These elements are known to form carbides that may refine the PAGS on the event the precipitate dissolution temperature is not reached [110] and therefore both the martensite and bainite structure will be refined. In addition, austenite could be strengthened through grain boundary strengthening and precipitation hardening leading to increased volume fraction of retained austenite [111,112]. However, the carbon content of the retained austenite may decrease because of the carbide precipitates [111,112], in turn increasing the driving force for bainite formation.…”
Section: Influence Of Chemical Compositionmentioning
confidence: 99%
“…In addition, austenite could be strengthened through grain boundary strengthening and precipitation hardening leading to increased volume fraction of retained austenite [111,112]. However, the carbon content of the retained austenite may decrease because of the carbide precipitates [111,112], in turn increasing the driving force for bainite formation. The alloy carbides themselves may act as potential nucleation sites, thereby potentially increasing the kinetics of subsequent transformations.…”
Section: Influence Of Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the steel exhibited increased strength but decreased total elongation relative to the base metal. However, Zhang et al found that microalloying improved the plasticity of the steel through an effective “phase transformation induced plasticity” (TRIP) effect from stable austenite [ 18 ]. Other researchers have found that microalloying elements can significantly increase strength but have a weak effect on plasticity [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming the difficulties in the application of QP steel can effectively promote the lightweight process of automobiles, realize energy saving and emission reduction, and improve the safety of automobiles [4,5]. The excellent mechanical performance of QP steels is owing to the transformation of the internal carbon-rich residual austenite (RA) into martensite (RA→M) during deformation, which induces plasticity by phase transformation and effectively enhances the plasticity of the steel [6][7][8]. In multiphase steels, the hard and soft phases may benefit the overall strength and plasticity, respectively, through an effective partitioning of stress/flow strain among the constituent phases during deformation [9,10].…”
Section: Introductionmentioning
confidence: 99%